ANALISIS PENGUNAAN KATA “ANJAY” YANG MENJADI KEBIASAAN GEN Z DAN GEN ALPHA DALAM BERKOMUNIKASI - Hardelia Rosidatul Adha; Aliyah Shafa N, Sinar Permata W.S., Abid Ubaidillah Akbar, Huda Hidayatulloh, Lintang Sinaring R (Jurnal Komunikasi, 2025)
The use of language in communication among the younger generation, especially Gen Z and Gen Alpha, shows changes in the form and function of everyday language. One prominent phenomenon is the use of the words "anjay" in their social interactions. These words were originally a form of emotional expression, rooted in the word "dog", a word that has a negative connotation in Indonesian culture. However, in the development of everyday language, especially among young people, these words have shifted in meaning and function. This study aims to determine how often and how influential the use of the words 'Anjay' and is in everyday life. In addition, this study also aims to determine the origin of the words 'Anjay'.